The Effect Of E-Marketing Mix On Purchase Decisions By Milenials Consumers Through Interest In Muslimah Fashion Products On Indonesian E-Commerce Platforms - Dian Wahyuni; Syaifuddin Syaifuddin; Nagian Toni (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Many teenagers in today's modern era think that conventional shopping has become a traditional buying and selling process that takes a lot of time and effort. So many millennial teenagers think shopping media applications can be a new facility for shopping. Therefore, it is necessary to know whether there is an effect of the e-marketing mix on purchasing decisions by millennial consumers through interest in Muslim fashion products on the Indonesian e-commerce platform. Collecting data in this study using quantitative methods. The results of the study show that e-marketing has a very large influence on millennial shopping decisions. With so many media showing advertisements about new items, teenagers are increasingly tempted to have them in order to fulfill their appearance. So it can be concluded that e-marketing has an influence on purchasing decisions by millennial consumers for Muslim fashion.